Fabrication and electrochemical OER activity of Ag doped MoO3 nanorods. (1st March 2020) - Jansi Rani, B.; Ravi, G.; Yuvakkumar, R.; Ameen, Fuad; AlNadhari, Saleh; Hong, S.I.
Abstract: Clean energy production using earth abundant electrocatalysts is still a complicated task to the researchers. In this study, we synthesized a rational and efficient MoO3 nanorod electrocatalysts for electrochemical water splitting process. Further, the role of Ag dopant and its concentration effect on physical and electrochemical performance of MoO3 host was studied. Slight lower angle shift of predominant crystal planes such as (120) and (021) was observed employing XRD studies for 5 and 10% Ag doped MoO3 nanorods. Other physical characteristics based on Ag dopant were reported. Well defined nanorod morphology of the samples was revealed through FESEM images. Excellent electrochemical psedocapacitive nature of 10% Ag induced MoO3 electrode was achieved as 695 F/g at low scan rate of 5 mV/s. Superior catalyzing ability of the same electrode was proposed as 344 mA/g at 10 mV/s scan rate with rapid and spontaneous reaction kinetics towards oxidation of water. Outstanding electrochemical catalyzing ability over 20 h was achieved as 97% for the recommended 10% Ag induced MoO3 nanorods electrode. The prepared electrode material is strongly suggested to design stable and efficient electrochemical energy conversion devices. Graphical abstract: Image 1 Highlights: Ag incorporation in Mo lattice of MoO3 was successfully achieved. Highest specific capacitance of 695 F/g was achieved at 5 mV/s scan rate. Excellent OER activity of 344 mA/g at 10 mV/s was achieved. Volmer-Herovsky reaction kinetics was achieved from 55 mV/dec Tafel slope. Electrochemical OER was achieved with 97% excellent stability over 20 h.